Italo Calvino : a journey toward postmodernism - Markey, Constance (Crosscurrents (Gainesville, Fla.), 1999)
"This primer for Italo Calvino fans surveys the international author in English translation, appraising his place in world literature and tracing his development as a postmodern writer from the start of his career during World War II to his death in 1985"--BOOK JACKET. "Constance Markey, who knew Calvino personally, correlates details of his life with the growth of his thinking and artistry, using summaries and analyses of his novels, short stories, and essays to underscore the link between his life and work."--Jacket